Science Learning Media for Elementary School Students - Nirwana Anas; Adi Hartono (Jurnal Penelitian Pendidikan IPA, 2024)
The use of media in learning will provide a learning experience for students because it can involve more senses and give them the freedom to interpret. This study aims to: develop android-based science learning media for elementary school students, obtain android-based science learning media suitable for elementary school students, and determine the response of elementary school students to android-based science learning media. This research is a Research and Development (R&D) study. The development procedure consists of six steps, namely: analysis of potential problems, data collection, product design, design validation, design revision, and product testing. The assessment instrument used is a questionnaire sheet to test the quality of Android-based science learning media products. The assessment of the quality of Android-based science learning media products is conducted by reviewers, peer reviewers, elementary school (SD/MI) teachers, and the response of sixth-grade students. The results of this development research are as follows: 1) Android-based science learning media products on the topic of living organism reproduction for sixth-grade students of SD/MI have been developed, 2) the Android-based science learning media for sixth-grade students of SD/MI on the topic of living organism reproduction has been assessed by reviewers, peer reviewers, and SD/MI teachers with a rating of "Very Good" (SB) with a score of 631 and a percentage rating of 86.85%, and 3) the response of sixth grade students of SD/MI to the Android-based science learning media falls within the "Agree and Strongly Agree" interval, resulting in a score of 635 with a rating percentage of 88.23%.